Um mercanismo para escalonamento de pacotes no uplink da rede LTE no contexto da comunicação máquina-a-máquina - Maia, Adyson Magalhães (2013)
Cellular networks are expected to play an important role in the future of Internet of Things (IoT) and in the Machine-to-Machine (M2M) communication with the LTE network gaining increasing highlights for this purpose. However, improvements in the LTE network are necessary because of the intrinsic characteristics of M2M communication, such as the large number of devices and the diversity of the requirements of their applications, which differen- tiate from the Human-to-Human (H2H) communication for which the network was initially designed. Among these improvements, it includes improving the uplink packet scheduler of LTE standard to dealing the M2M communication and meets your requirements without serious impacts on the H2H communication. This work proposes a mechanism for the uplink packet scheduler in the context of M2M communication that uses current and past information from the network and each device to satisfy their requirements of Quality of Service (QoS), avoid the problem of starvation and control the congestion caused by these devices. The results indicate that the proposal can reduce the impact of the M2M communication over the H2H and ensure justice in resource allocation, however, the level of satisfaction of QoS requirements decreases with increasing of H2H traffic.